The application of L-theanine for patients with mental health conditions - a review - Michał; Beata Getka; Justyna Kwiecień; Kinga Przyborowska; Katarzyna Wiejak; Mateusz Rukat (Kazimierz Wielki University, 2024)
L-theanine is an amino-acid found in green tea (Camellia sinensis), a beverage consumed by people all around the world. Its chemical structure is similar to L-glutamic acid. L-theanine acts as an antagonist of AMPA and kainate receptors as well as partial co-agonist of the NMDA receptors. The application may be associated with several health benefits, such as improvements in cognition, reduction of stress and anxiety-like symptoms. Although the dosage of L-theanine in green tea, which is around 20 mg per tea, is not very likely to have meaningful impact on mental health, supplementation of doses 200-400 mg/day has shown some promising advantages. Despite some evidence towards beneficial impact of L-theanine on mental health, longer-term and larger cohort clinical studies are required in order to justify its application for patients suffering from such diseases as anxiety, depression, bipolar disorder, schizophrenia and sleep disorders. What is more, it is more possible to act as a therapy augmentation in particular cases, rather than conventional therapy replacement.